The Franciscan Raez and the unification of Quechua - Cerrón-Palomino, Rodolfo (1985)
This article offers an interpretation of the linguistic work of the Franciscan huancaino José Francisco María Ráez as a typical illustration of what is modernly called Corpus planning. At the crossroads of uniting or dividing Quechua at the level of written representation, the Franciscan opts for the first alternative, showing the "harmony" between Quechua in the Mantaro Valley (Quechua 1) and Ayacucho (Quechua 11) . Such an option, contrary to popular belief, is never free from deeply ideological and political motivations, a fact that should be taken into account in the current debate on the scriptural development of Quechua.